CO Gas Detection on Pt∣YSZ∣Pt Solid Electrolyte Sensors by Methods Based on Dynamic Voltage Variations. Issue 11 (9th November 2021) - Ruchets, Anastasiya; Donker, Nils; Zosel, Jens; Schönauer-Kamin, Daniela; Moos, Ralf; Guth, Ulrich; Mertig, Michael
Abstract : CO detection with a dynamically operated solid-electrolyte sensor (SES) was investigated at 700 °C–750 °C in the concentration range between 0 and 150 vol.-ppm CO. Dynamic voltage variations by electrochemical impedance spectroscopy, cyclic voltammetry, and square-wave voltammetry showed a pronounced sensitivity to the presence of carbon monoxide in gas mixtures in the investigated concentration range at optimized experimental conditions. Specific differences of CO detection in reducing and oxidizing conditions are described in detail. Selectivity to oxygen, nitrogen monoxide, and hydrogen are discussed. Since the methods can also be used to selectively determine oxygen, nitrogen oxide and hydrogen, they open up new possibilities for complex multiple gas analysis.